2016
DOI: 10.1590/0102-6720201600030005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Ingestion of Wine on the Glycemic, Lipid and Body Weight Homeostasis in Mice

Abstract: Background: The health benefits associated with moderate wine consumption, as with ethanol and phenolic compounds, include different mechanisms still little understandable. Aim: Evaluate glycemic and weight variations, and the deposit of triglycerides, cholesterol and liver glycogen with red wine consumption. Methods: 60 ApoE knockout mice were divided into three groups of 20: Wine Group (WG), Ethanol Group (EG) and Water Group (WAG). They received daily: WG 50 ml of wine and 50 ml water; EG 6 ml ethanol and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Additionally, previous studies have demonstrated that the clinical function outcomes of patients with acute ischemia can be determined by measuring the IC volume [ 26 , 27 ]. Our findings corroborated previous studies [ 28 30 ] by showing that the IC volume was significantly smaller in the favorable outcome group.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, previous studies have demonstrated that the clinical function outcomes of patients with acute ischemia can be determined by measuring the IC volume [ 26 , 27 ]. Our findings corroborated previous studies [ 28 30 ] by showing that the IC volume was significantly smaller in the favorable outcome group.…”
Section: Discussionsupporting
confidence: 92%